Factors predictive of long-term mortality in lupus nephritis: a multicenter retrospective study of a Japanese cohort. (March 2019) - Ichinose, K; Kitamura, M; Sato, S; Fujikawa, K; Horai, Y; Matsuoka, N; Tsuboi, M; Nonaka, F; Shimizu, T; Fukui, S; Umeda, M; Koga, T; et al.
Background: Lupus nephritis (LN) is a major determinant of mortality in systemic lupus erythematosus (SLE). Here we evaluated the association between complete renal response (CR) and mortality in LN. Methods: We retrospectively analyzed the cases of 172 of 201 patients with LN for whom data on the therapeutic response at 6 and 12 months after induction therapy were available. The patients underwent a renal biopsy at Nagasaki University Hospital and community hospitals in Nagasaki between the years 1990 and 2016. We determined the CR rates at 6 and 12 months after induction therapy initiation and evaluated the predictive factors for CR and their relationship with mortality. We performed univariate and multivariable competing risks regression analyses to determine the factors predictive of CR. The patients' survival data were analyzed by the Kaplan–Meier method with a log-rank test. Results: The median follow-up duration after renal biopsy was 120 months (interquartile range: 60.3–191.8 months). The 5-, 10-, 15- and 20-year survival rates of our cohort were 99.3, 94.6, 92.0 and 85.4%, respectively. During follow-up, nine patients (5.2%) died from cardiovascular events, infection, malignancy and other causes. The multivariate analysis revealed that the following factors were predictive of CR. At 6 months: male gender (odds ratio (OR) 0.23, 95% confidence interval (CI) 0.08–0.65, p  = 0.0028), proteinuria (g/gCr) (OR 0.83, 95% CI 0.71–0.97, p  = 0.0098) and index of activity (0–24) (OR 0.84, 95% CI 0.71–0.99, p  = 0.0382). At 12 months: male gender (OR 0.25, 95% CI 0.09–0.67, p  = 0.0043) and index of activity (0–24) (OR 0.82, 95% CI 0.69–0.98, p  = 0.0236). The Kaplan–Meier analysis showed that compared to not achieving CR at 12 months, achieving CR at 12 months was significantly correlated with the survival rate (OR 0.18, 95% CI 0.04–0.92, p  = 0.0339). Conclusions: Our results suggest that the survival rate of patients with LN is associated with the achievement of CR at 12 months after induction therapy, and that male gender and a higher index of activity (0–24) are the common predictive factors for failure to achieve CR at 6 and 12 months.